Serum retinol-binding protein 4 levels in polycystic ovary syndrome. Issue 6 (June 2019) - Lingaiah, Shilpa; Morin-Papunen, Laure; Piltonen, Terhi; Sundström-Poromaa, Inger; Stener-Victorin, Elisabet; Tapanainen, Juha S
Abstract : Objective: Serum levels of retinol-binding protein 4 (RBP4), an adipokine thought to affect systemic insulin sensitivity, were compared between women with polycystic ovary syndrome (PCOS) and non-PCOS controls to evaluate the association of RBP4 with clinical, hormonal and metabolic parameters of PCOS. Subjects and methods: Serum RBP4 levels were analysed in 278 women with PCOS (age range 18–57 years) and 191 non-PCOS controls (age 20–53 years) by enzyme-linked immunosorbent assay. Results: Serum levels of RBP4 were increased in women with PCOS compared with control women in the whole population (45.1 ± 24.0 (s.d. ) vs 33.5 ± 18.3 mg/L, P  < 0.001). Age-stratified analysis showed that serum RBP4 levels were increased in women with PCOS aged ≤30 years compared with controls (47.7 ± 23.5 vs 27.1 ± 10.4 mg/L, P  < 0.001), whereas no significant differences were seen in the other age groups. No significant correlations of RBP4 were seen with either steroids or indices of insulin resistance. Conclusions: Although serum RBP4 levels were increased in younger women with PCOS compared with age-matched non-PCOS controls, RBP4 does not seem to be a good marker of insulin resistance or other metabolic derangements in women with PCOS.